2017
DOI: 10.1098/rsos.160662
|View full text |Cite
|
Sign up to set email alerts
|

The interpretation of mu suppression as an index of mirror neuron activity: past, present and future

Abstract: Mu suppression studies have been widely used to infer the activity of the human mirror neuron system (MNS) in a number of processes, ranging from action understanding, language, empathy and the development of autism spectrum disorders (ASDs). Although mu suppression is enjoying a resurgence of interest, it has a long history. This review aimed to revisit mu's past, and examine its recent use to investigate MNS involvement in language, social processes and ASDs. Mu suppression studies have largely failed to pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
117
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 147 publications
(126 citation statements)
references
References 109 publications
(252 reference statements)
8
117
0
1
Order By: Relevance
“…In other words; MEP recordings of mirror system functioning during TMS are obtained at the level of the muscle, reflecting corticospinal processes, whereas the EEG mu rhythm mainly reflects central cortical activity. Although both techniques have been shown to reliably capture mirror system activation (see reviews by Fadiga, Carighero & Olivier, 2005;Hobson & Bishop, 2017), it has been suggested thatconsidering these substantial differences in neurophysiological underpinnings -both techniques might target different aspects of the mirror system. In this respect, the neural processes triggered by action observation have been proposed to be layered in several hierarchically organized functional levels (Grafton & Hamilton, 2007;Kilner, Friston, & Frith, 2007).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In other words; MEP recordings of mirror system functioning during TMS are obtained at the level of the muscle, reflecting corticospinal processes, whereas the EEG mu rhythm mainly reflects central cortical activity. Although both techniques have been shown to reliably capture mirror system activation (see reviews by Fadiga, Carighero & Olivier, 2005;Hobson & Bishop, 2017), it has been suggested thatconsidering these substantial differences in neurophysiological underpinnings -both techniques might target different aspects of the mirror system. In this respect, the neural processes triggered by action observation have been proposed to be layered in several hierarchically organized functional levels (Grafton & Hamilton, 2007;Kilner, Friston, & Frith, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…There are several methodological considerations to be taken into account when evaluating the EEG mu rhythm. For an in-depth discussion, the interested reader is referred to reviews by Hobson & Bishop (2017) and Cuevas, Cannon, Yoo, & Fox (2014). Here, we briefly touch upon some relevant issues relevant that motivated our adopted design.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The fourth theoretically-relevant EEG index is Mu suppression. The is measured at central electrodes, and its suppression assumingly reflects the activation of sensorimotor areas (Fox et al, 2016;Hobson and Bishop, 2017). Mu suppression occurs when an individual either performs or observes motor actions, and is considered as a valid measure of MNS activity (Fox et al, 2016).…”
Section: Introductionmentioning
confidence: 99%